ḤURRIYAT AL-TAṢARRUF DALAM AMALAN PEMILIKAN TANAH DI FELDA : Ḥurriyat al-Taṣarruf in FELDA’s Land Ownership Practice - Mohd Razif, Nor Fahimah; Marjani, Muhamat Faizal; Ali, Abdul Karim; Mustapha, Ariyanti (Jurnal Syariah, 2024)
The ownership of land in FELDA (Federal Land Development Authority) is unique due to several restrictions arising from legal provisions and agreements. These restrictions have led to various interpretations regarding the practice of land ownership in FELDA, thereby denying the element of ḥurriyat al-taṣarruf (freedom to conduct any transaction). Therefore, the objective of this study is to explain the concept of ḥurriyat al-taṣarruf and its controlling instruments according to Islamic principles, describe the concept of land ownership in FELDA, and analyze the existence of ḥurriyat al-taṣarruf in land ownership practices within FELDA. A qualitative methodology with a grounded theory research approach is used through continuous comparison of all the obtained data from documents and interviews. The study finds that the restrictions enacted in the GSA Act 1960 represent taṣarruf al-imām (actions of the leader) to protect the economic interests of the people. Although restrictions in ownership and rights exist in the practice of land ownership in FELDA, this does not negate the existence of ḥurriyat al-taṣarruf, as evidenced in the practices of land transfer, inheritance, waqf land, and agricultural land management. Further studies need to be conducted, particularly in suggesting improvements in land ownership practices in FELDA based on the fiqh framework.